PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW UNTUK MENINGKATKAN MOTIVASI DAN PRESTASI BELAJAR PESERTA DIDIK (Studi Pada Mata Pelajaran Bahasa Arab Kelas VIII MTs Negeri 1 Pagar Alam) - Darudin Darudin (UNIB Press, 2021)
The purpose of this study was to describe the application of the Jigsaw cooperative learning model to increase the motivation and learning achievement of students in Arabic class VIII subjects at MTs Negeri 1 Pagar Alam. The model used in this research is classroom action research with experiments. The subjects in this study were 96 students of class VIII MTs Negeri 1 Pagar Alam, of which 32 students were class VIII.3 as an action class, as a sample the experimental class was class VIII.1, totaling 32 participants. students while the control class was class VIII.2, totaling 32 students for data collection techniques using observation sheets and tests, the collected data were analyzed using averages and t-test. The results of this study concluded that learning with the application of the type of jigsaw cooperative learning model can increase the motivation and achievement of students in learning, especially in Arabic at MTs Negeri 1 Pagar Alam